Accelerating analysis for metabolomics, drugs and their metabolites in biological samples using multidimensional gas chromatography. (May 2009) - Mitrevski, Blagoj S; Kouremenos, Konstantinos A; Marriott, Philip J
Gas chromatography (GC) with mass spectrometry (MS) is one of the great enabling analytical tools available to the chemical and biochemical analyst for the measurement of volatile and semi-volatile compounds. From the analysis result, it is possible to assess progress in chemical reactions, to monitor environmental pollutants in a wide range of soil, water or air samples, to determine if an athlete or horse trainer has contravened doping laws, or if crude oil has migrated through subsurface rock to a reservoir. Each of these scenarios and samples has an associated implementation method for GC–MS. However, few samples and the associated interpretation of data is as complex or important as biochemical sample analysis for trace drugs or metabolites. Improving the analysis in both the GC and MS domains is a continual search for better separation, selectivity and sensitivity. Multidimensional methods are playing important roles in providing quality data to address the needs of analysts.